Selected Abstracts of the 19th International Workshop on Neonatology and Pediatrics; Cagliari (Italy); October 18-21, 2023 - - (Hygeia Press di Corridori Marinella, 2023)
Selected Abstracts of the 19th International Workshop on Neonatology and Pediatrics; Cagliari (Italy); October 18th-21st, 2023 FROM WOMB TO AGING, FROM MEDICAL HISTORY TO ARTIFICIAL INTELLIGENCE   The Workshop has been organized with the patronage of UENPS (Union of European Neonatal and Perinatal Societies), UMEMPS (Union of Middle-Eastern and Mediterranean Pediatric Societies), SIP (Italian Society of Pediatrics), SIN (Italian Society of Neonatology), SIAIP (Italian Society of Pediatric Allergology and Immunology), SIPO (Italian Society of Hospital Pediatricians), SI-DOHaD (Italian Society of DOHaD [Developmental Origins of Health and Disease]), SIBioC (Italian Society of Clinical Biochemistry), SIPPS (Italian Society of Preventive and Social Pediatrics), S.I.P.Ped. (Italian Society of Pediatric Psychology), SIGIA (Italian Society of Gynecology of Infancy and Adolescence), CONAPP (Italian Association of Chiefs of Pediatric Divisions), SIN-INF (Italian Society of Neonatal Nursing), IAPS (Italian Arabian Society of Pediatrics), Alfred Nobel's Study Center, GNNNP (Norman Group of Neonatal and Pediatric Nephrology), IRPS (Italian Romanian Pediatric Society), RSP (Romanian Society of Pediatrics), IPMC (International Pedia Mediterranean Conference).   ABS 1. TOTAL HEAD GROWTH IN PATIENTS WITH PKU DIAGNOSED BY NEWBORN SCREENING TEST • B.A. Ibrahim, S.A. Hussein, A.E. Ali, R.H. Baaker ABS 2. ARTIFICIAL INTELLIGENCE AND POSTPARTUM DEPRESSION: THE "TALKING ABOUT" ALGORITHM • V. Fanos, A. Dessì, L. Deledda, A. Lai, P. Ranzi, I. Avellino, F. Marinaro, S. Petza, R. Pintus, G. Oliverio, S.G. Vitale, S. Angioni, A. Colangelo ABS 3. PEDIATRIC ONCOLOGICAL SPONDYLOLISTHESIS: THE CONTRIBUTION OF PHYSICAL AND REHABILITATION MEDICINE AND ORTHODONTICS • A. Scribante, M. Pellegrini, M. Ghizzoni, M.G. Nardi, B. Rocca, M. Monticone ABS 4. A NEW PEDIATRIC INITIATIVE FOR CLINICAL GOVERNANCE: THE ITALIAN ASSOCIATION OF CHIEFS OF PEDIATRIC DIVISIONS • S. Rugolotto, E. Cortis, C. Cavalli, A. Cualbu, L. Martemucci, G. Parisi, G. Pennoni, E. Ponticiello, V. Tipo, D. Minasi ABS 5. A RARE VARIANT OF BECKER MUSCULAR DYSTROPHY • B.M. Trapani ABS 6. HUMAN HERPESVIRUS-6 INFECTION AS A CAUSE OF RHABDOMYOLYSIS IN TODDLER • M.E. Picciau, P. Beretta, V. Ibba, S. Mameli, F.F. Comisi, S. Savasta ABS 7. BREASTFEEDING FOLLOW-UP: FROM BIRTH TO 6 MONTHS OF CORRECT AGE IN A COHORT OF VLBW NEWBORNS • C. Peila, L. Riboldi, S. Deantoni, C. Tricerri, E. Bertino, A. Coscia ABS 8. SIXTH CRANIAL NERVE PALSY: NOT ALL IS AS IT SEEMS! • S. Galzignato, F. Marino, G. Margheri, F. Rigon, S. Bellonzi, C. Lorenzetto, G. Passarella, F. Sansone, E. Cuppini, S. Rugolotto ABS 9. THE EMERGENCE OF CONSCIOUSNESS-STATE DEPENDENT COMPLEXITY: SEPs AND PERTURBATION COMPLEXITY INDEX IN NEWBORNS AND YOUNG INFANTS • E. Sportaro, C. Peila, L. Riboldi, S. Deantoni, A. Rossi Sebastiano, I. Ronga, K. Poles, S. Russo, A. Comanducci, A. Coscia, E. Bertino, A. Pigorini, F. Garbarini ABS 10. URINARY GC-MS METABOLOMICS OF SARDINIAN CYSTIC FIBROSIS PATIENTS REVEALS UNIQUE MUTATION-CLASS DEPENDENT SIGNATURES • M. Spada, A. Noto, C. Piras, G. Diana, K.K. Kopeć, V. Fanos, L. Atzori, M. Zanda ABS 11. EXPLORING THE RELATIONSHIP AMONG MRI SCORING SYSTEMS AND NEURODEVELOPMENTAL OUTCOME AT 2 YEARS IN INFANTS WITH HIE AFTER THERAPEUTIC HYPOTHERMIA • M. Vendemmia, C.V. Lambiase, G. Mansi, G. Terrone, D. Pacella, C. Paolella, A. Romano, A. Romano, C. Colinet, R. Russo, F. Carraturo, L. Capasso, F. Raimondi ABS 12. A FEMALE INFANT WITH GESTATIONAL AGE 22+4 WEEKS. A CASE REPORT • E. Tsianaka, K. Angelou, M. Diakosavvas, A. Kontogiannie, A. Charitou ABS 13. DIAGNOSTIC-THERAPEUTIC PATHWAYS OF NTDs • A. Bertini, C.M. Manca, M.C. Mulvoni, M. Marsan, P. Sechi, V. Manca, M. Zanda, F. Zurrida, M. Balzarini, G. Masnata ABS 14. IDIOPATHIC SCOLIOSIS: HOW ARTIFICIAL INTELLIGENCE CAN ASSIST CURRENT AND FUTURE CLINICAL PRACTICE • G. Uccheddu, K.K. Kopeć ABS 15. CLINICAL-PATHOLOGICAL CORRELATIONS BETWEEN ABNORMAL PLACENTAL VASCULAR DEVELOPMENT AND UNFAVORABLE NEONATAL OUTCOME: A MULTIFACTORIAL STUDY • V. Chessa, M. Vincis, A. Canino, C. Gerosa, D. Fanni ABS 16. GASTROINTESTINAL DISORDERS IN ATRX SYNDROME: HOW TO DEAL WITH THEM? • A. Abis, F.F. Comisi, E. Esposito, C. Melis, C. Soddu, M. Marica, S. Savasta ABS 17. ACCESSES TO PEDIATRIC EMERGENCY UNIT CAUSED BY DOMESTIC ACCIDENT: A RETROSPECTIVE STUDY • P. Ajovalasit, A. Carollo ABS 18. HYALINE MEMBRANE DISEASE. HALLMARK OF NEONATAL RESPIRATORY DISTRESS SYNDROME • A. Canino, V. Chessa, M. Vincis, D. Fanni, C. Gerosa ABS 19. IMPACT OF TWINNING ON SHORT-TERM CLINICAL OUTCOMES OF PRETERM INFANTS: A PROTOCOL STUDY • L. Riboldi, C. Peila, D. Ferri, E. Spada, E. Bertino, A. Coscia ABS 20. PHENOTYPICAL EXPRESSION OF AHDC1 DE NOVO TRUNCANT MUTATIONS: A RARE DISEASE • B.M. Trapani ABS 21. IS THE IRRITABLE BOWEL SYNDROME A MANIFESTATION OF DISTRESS IN PARENTS OF PRETERM INFANTS? PRELIMINARY FINDINGS FROM A LONGITUDINAL FOLLOW-UP STUDY • C.V. Lambiase, G. Mansi, M. Pesce, G. Sarnelli, M.C. Zurlo, S. Salomè, S. Russo, F. Carraturo, F. Raimondi, L. Capasso ABS 22. EXPERIMENTAL PILOT PROJECT: "LET'S HELP EACH OTHER: INTEGRATED PSYCHOLOGIST-PEDIATRICIAN HEALTH INTERVENTIONS IN THE PEDIATRIC first aid post OF AUGUSTA". A SERVICE FOR FAMILIES • A. Donzelli, R. Castro, D. Carrabino ABS 23. A SEVERE HYPERLACTACIDEMIA IN A DOLL FACE INFANT: DIAGNOSIS OF GLYCOGENOSIS 1B • M. Balzarini, M. Toto, P. Currao, L. Manunza, M. Tiddia, D. Manunza, G. Masnata, S.R. Giglio, M. Zanda ABS 24. LESS INVASIVE SURFACTANT ADMINISTRATION (LISA). RESULTS IN APPLYING THIS METHOD IN OUR NICU (BETWEEN APRIL 2019 AND DECEMBER 2022) • E. Tsianaka, K. Angelou, M. Diakosavvas, A. Kontogiannie, A. Charitou ABS 25. MONITORING OF URINARY TRACT COMPLICATIONS IN PATIENTS WITH SPINA BIFIDA • M.C. Mulvoni, C.M. Manca, A. Bertini, M. Marsan, P. Sechi, V. Manca, G. Masnata ABS 26. PEDIATRIC FUNCTIONAL NEUROLOGICAL DISORDER: THE COMMUNICATION OF DIAGNOSIS IS THE START OF THE TREATMENT • D. Suglia, S. Biscuola, F. Rigon, S. Rugolotto ABS 27. THE IMPORTANCE OF FINE-NEEDLE ASPIRATION CYTOLOGY IN THE PREOPERATIVE DIAGNOSIS OF PEDIATRIC MALIGNANT THYROID NODULES: A CASE SERIES • V. Chessa, M. Vincis, A. Canino, E. Noto, E. Sanna, M.L. Altana, G. Pinna, P.G. Calò, L. Secci, C. Gerosa, D. Fanni, M.L. Lai ABS 28. UNDERSTANDING ELEMENTARY PLACENTAL LESIONS: DISTINGUISHING BETWEEN PATHOLOGICAL AND PHYSIOLOGICAL CHANGES IN THE CLINICAL PRACTICE • C. Gerosa ABS 29. USE OF SELUMETINIB IN PEDIATRIC PATIENTS WITH NF1 AND PLEXIFORM NEUROFIBROMAS • G.M. Cortes, A. Piras, C. Tognazzi, P. Sulas, C. Soddu, S. Savasta ABS 30. A CASE STUDY OF THE EUROPEAN LIFE MILCH PROJECT: CORRELATION BETWEEN MATERNAL NUTRITION, BREASTFEEDING AND GROWTH • E. Sanna, V. Di Chiara, R. Pintus, V. Fanos, M.E. Street, P. Palanza, A.M. Papini, S. Petza, A. Dessì ABS 31. PEDIATRIC ONCOLOGICAL PAIN: THE INFLUENCE ON THE POSTURE OF THE HEAD AND THE SPINE • A. Scribante, M. Pellegrini, M. Ghizzoni, M.G. Nardi, B. Rocca, M. Monticone ABS 32. USE OF GRIFFITHS III SCALES IN A COHORT OF PRETERM AND VLBW INFANTS: EVALUATION OF NEURODEVELOPMENTAL OUTCOMES • G. Acuto, C. Peila, L. Riboldi, M. Capitanio, D. Ferri, E. Bertino, E. Spada, A. Coscia ABS 33. TRAUMA IN PARENTS AND CHILDREN IN CASE OF HOSPITALIZATION OF THE NEWBORN IN THE NEONATAL INTENSIVE CARE UNIT • S. Petza, R. Pintus, A. Dessì, V. Fanos ABS 34. AN ITCH... THAT GOES TO THE BONE • S. Galzignato, F. Marino, G. Margheri, F. Rigon, S. Bellonzi, C. Lorenzetto, G. Passarella, F. Sansone, E. Cuppini, S. Rugolotto ABS 35. THE IMPORTANCE OF PLACENTAL ANALYSIS IN INTRAUTERINE GROWTH RETARDATION • M. Vincis, V. Chessa, A. Canino, L. Nonnis, E. Sanna, D. Fanni, C. Gerosa  ABS 36. A RARE CASE OF URTICARIA PIGMENTOSA • P. Baldussu, L. Nonnis, E. Noto, J. Caschili, R. Murru, M.L. Corbeddu, C. Ferreli, J. Anedda, C. Gerosa, D. Fanni, L. Pilloni ABS 37. EUROPEAN LIFE MILCH PROJECT: MATERNAL OBESITY AND NEONATAL GROWTH, BREASTFEEDING AND NEURODEVELOPMENT • V. Di Chiara, E. Sanna, S. Petza, A. Dessì, M.E. Street, P. Palanza, A.M. Papini, V. Fanos ABS 38. RARE DISEASES AND COMPLICATIONS: DEEP VEIN THROMBOSIS AND POMC DEFICIENCY. A CASE REPORT • C. Melis, F.F. Comisi, A. Abis, E. Esposito, C. Soddu, M. Marica, S. Savasta ABS 39. HEMORRHAGIC DIARRHEA: WHEN PURPURA TAKES OVER • F. Marino, E. Visonà, S. Galzignato, G.